VAGUENESS IN POLISH AND AMERICAN CRIMINAL LAW LANGUAGE AND DEFINITIONS (A STUDY OF POLISH AND US LEGAL SYSTEMS) - STRĘBSKA, Katarzyna (Comparative Legilinguistics, 2015)
The paper below intends to present and evaluate the theories of vagueness in the language of criminal law as exemplified in legal definitions. In the theory aimed to facilitate the task of interpretation of laws and statutes, in practice legal definitions they may be vague themselves, a phenomenon which either jeopardizes the stability of law and order, or makes law more flexible and compliant with the changing status quo. How one approaches the matter would depend upon a variety of factors. Among them we will find the branch of law or the type of the legal system. As far as criminal law is concerned, vague expressions are to be avoided. However, some legal systems “stigmatize” them more than others. In the American legal system the “void-for-vagueness” doctrine best illustrates the negative attitude of law enforcement institutions towards vague and unclear language. In the Polish law, on the other hand, it is not so explicitly criticized. Leaving room for free interpretation, vague language may prove a useful tool if literal interpretation defies the so-called “common-sense” understanding (very often referred to in works dedicated to law interpretation). Once a review of both legal systems is made, the author tries to arrive at a definite conclusion whether we should treat vagueness in the language of criminal provisions as something sought-for or rather undesirable.